Malaysian Bee Bread Attenuates Apoptosis and Improves Cell Proliferation in Testis of High-Fat Diet-Induced Obese Rats - Suleiman, Joseph Bagi; Bakar, Ainul Bahiyah Abu; Mohamed, Mahaneem (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: Obesity has been reported to impair male reproductive function and testicular apoptosis while bee bread has been traditionally consumed to enhance male fertility. Objective: The objective of this study was to determine the effects of Malaysian bee bread on apoptosis and proliferation of testicular germ cells in high-fat diet-induced obese rats. Methods: Twenty-four adult male Sprague Dawley rats weighing between 250-300 g were randomised into four groups (n=6/group), namely normal control (NC), high-fat diet (HFD), HFD plus bee bread (HFD+B) and HFD plus an anti-obesity drug orlistat (HFD+O) groups. Bee bread (0.5g/kg/day) and orlistat (10 mg/kg/day) were suspended in distilled water and given by oral gavage for 12 weeks. Markers for apoptosis and proliferation of testicular germ cells were assessed. Results: mRNA transcript levels of caspase-3, caspase-8, caspase-9, p53 and Bax/Bcl2 ratio in the testis of HFD group were significantly increased while immunohistochemical staining of cleaved caspase-3 increased and proliferating cell nuclear antigen (PCNA) immunoexpress ions decreased relative to NC group. Treatment with bee bread significantly decreased the apoptotic markers, significantly decreased mRNA transcript levels of anti-apoptotic markers (Bcl2) and increased PCNA immunoexpression in HFD+B, relative to NC group and HFD+O. Conclusion: Bee bread improved proliferation of testicular germ cells by attenuating apoptosis in high- fat diet-induced obese male rats. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 44